The integration of technology in learning and teaching English, Champasack University - LUANGSOMBATH, Soulichanh; PHENGSOM2, Manivone; KEOPASEUTH, Bounmee; SIDAVONG, Silavanh; NOUTHAPHONE, Thiphachanh; PHALYCHAN, Bounmy; PHOTHILATH, Ammalin; PHOMPHITHAK, Chansy; SYSAVATH, Somphane (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
Integrating technology into learning and teaching facilitates learning and learning process. Technology have drastically changed the ways of learning and teaching English. Technology provides opportunity both students and lecturers to exposure technology tools in education. Technology has effectively raised ability in learning English. It provides greater flexibility, convenience, and accessibility in learning platforms such Google apps and other applications. Thus, lectures at Champasack University integrated technology tool into their instruction like Google application to deliver their teaching performance. The target group for this study is English lectures at Champasack University. Data collection is a set of questionnaire designed and administered to participants via Google form. The questionnaire is designed as multiple choice and checkbox options. Data were analyzed with SPSS program to obtain the result of the study. All questions made the distribution of answers formatted into the table for each question. Data from the table were interpreted respectively. The survey discovered that technology-facilitated learning and teaching English. Technology integration can alter the learning and teaching method. It raised motivation and built an energetic learning environment. Technology allowed more opportunities for interaction between students and teachers. It encouraged collaboration, handled teaching plan, created the test, and tracked students’ learning progress. However, participants encountered with poor internet signal from the host internet distribution which contributed to difficulty of accessing learning and teaching platform.